AllergenOnline: A peer‐reviewed, curated allergen database to assess novel food proteins for potential cross‐reactivity. Issue 5 (3rd March 2016) - Goodman, Richard E.; Ebisawa, Motohiro; Ferreira, Fatima; Sampson, Hugh A.; van Ree, Ronald; Vieths, Stefan; Baumert, Joseph L.; Bohle, Barbara; Lalithambika, Sreedevi; Wise, John; Taylor, Steve L.
Abstract : The AllergenOnline database is a risk assessment tool to identify novel proteins in genetically modified organisms or processed foods that might be sufficiently identical to an allergen based on FASTA to suspect potential cross‐reactivity, requiring allergen‐specific serum IgE testing. The AllergenOnline.org is updated annually with sequences associated with published proof of allergy based on pre‐defined criteria as interpreted by a panel of experts. Criteria include definition of protein characteristics, allergic test subjects, IgE binding, and evidence of biological activity (Basophil or in vivo tests). Abstract : Scope: Increasingly regulators are demanding evaluation of potential allergenicity of foods prior to marketing. Primary risks are the transfer of allergens or potentially cross‐reactive proteins into new foods. AllergenOnline was developed in 2005 as a peer‐reviewed bioinformatics platform to evaluate risks of new dietary proteins in genetically modified organisms (GMO) and novel foods. Methods and results: The process used to identify suspected allergens and evaluate the evidence of allergenicity was refined between 2010 and 2015. Candidate proteins are identified from the NCBI database using keyword searches, the WHO/IUIS nomenclature database and peer reviewed publications. Criteria to classify proteins as allergens are described. Characteristics of the protein, the source and human subjects, test methods and results are evaluated by our expert panel and archived. Food, inhalant, salivary, venom, and contact allergens are included. Users access allergen sequences through links to the NCBI database and relevant references are listed online. Version 16 includes 1956 sequences from 778 taxonomic‐protein groups that are accepted with evidence of allergic serum IgE‐binding and/or biological activity. Conclusion: AllergenOnline provides a useful peer‐reviewed tool for identifying the primary potential risks of allergy for GMOs and novel foods based on criteria described by the Codex Alimentarius Commission (2003).